Protective anti-tumor vaccination against glioblastoma expressing the MHC class II transactivator CIITA - Celesti, Fabrizio; Gatta, Andrea; Shallak, Mariam; Chiaravalli, Anna Maria; Cerati, Michele; Sessa, Fausto; Accolla, Roberto S.; Forlani, Greta (Frontiers in Immunology, 2023)
Glioblastoma is the most malignant tumor of the central nervous system. Current treatments based on surgery, chemotherapy, and radiotherapy, and more recently on selected immunological approaches, unfortunately produce dismal outcomes, and less than 2% of patients survive after 5 years. Thus, there is an urgent need for new therapeutic strategies. Here, we report unprecedented positive results in terms of protection from glioblastoma growth in an animal experimental system after vaccination with glioblastoma GL261 cells stably expressing the MHC class II transactivator CIITA. Mice injected with GL261-CIITA express de novo MHC class II molecules and reject or strongly retard tumor growth as a consequence of rapid infiltration with CD4+ and CD8+ T cells. Importantly, mice vaccinated with GL261-CIITA cells by injection in the right brain hemisphere strongly reject parental GL261 tumors injected in the opposite brain hemisphere, indicating not only the acquisition of anti-tumor immune memory but also the capacity of immune T cells to migrate within the brain, overcoming the blood–brain barrier. GL261-CIITA cells are a potent anti-glioblastoma vaccine, stimulating a protective adaptive anti-tumor immune response in vivo as a consequence of CIITA-driven MHC class II expression and consequent acquisition of surrogate antigen-presenting function toward tumor-specific CD4+ Th cells. This unprecedented approach for glioblastoma demonstrates the feasibility of novel immunotherapeutic strategies for potential application in the clinical setting.